MULTILOCI SEQUESTERANT STRAINS OF STREPTOCOCCUS PNEUMONIAE ISOLATED FROM ELDERLY PATIENTS WITH COMMUNITY ACQUIRED PNEUMONIA - A. V. Martynova; L. A. Balabanova; O. A. Chulakova (Бюллетень сибирской медицины, 2014)
Comuunity-acquired pneumonias in aged patients is the significant epidemiology problem for the public health of almost all the countries. Even more important the problem of microbiological monitoring and epidemiology surveillance for the S. pneumoniae strains as one of the ubiquitous pathogens causing as the community-acquired pneumonias as well the other infections of respiratory tract, what defines their different epidemiological meaning.Multilocus sequence typing is the perspective method of molecular epidemiological surveillance allowing to define the epidemiologically dangerous clones of the ubiquitous microorganisms as Streptococcus pneumomiae. The aim of our research was to conduct the multilocus sequence typing of pneumococci strains isolated in patients with community acquired pneumonias, bronchitis in aged patients.Materials and methods. There were taken 14 strains of S. pneumoniae, isolated in patients with community-acquired pneumonias (seven of them were multiresistant), eight strains were isolated from patients with the chronical onstructive lung diseases and four strains from carriers. Multilocus sequence typing was conduected according to method to M.C. Enright and B.G. Spratt (1998).Results. The strains, isolated in all populations were the related isolates of the species S. pneumoniae, the most of them had the unique genotype defining the sequence type for every strain. There were 6 strains of Taiwan 19F-14 genotype from 14 strains isolated in aged patients with community-acquired pneumonia. Among strains isolated from carriers there were prevailing the strai of R6 genotype.Conclusion. Multilocus sequence typing allows to identify the new genotypes and to prognose the appearing of epidemiologically dangerous strains with new peculiarities.